Diabetes, periodontitis, and cardiovascular disease: towards equity in diabetes care - Constanza Serón; Constanza Serón; Pablo Olivero; Pablo Olivero; Nicolás Flores; Nicolás Flores; Benjamín Cruzat; Benjamín Cruzat; Francisca Ahumada; Francisca Ahumada; François Gueyffier; Ivanny Marchant; et al. (Frontiers Media S.A., 2023)
Type 2 diabetes and its associated cardiovascular risk is an escalating epidemic that represents a significant public health burden due to increased morbidity and mortality, disproportionately affecting disadvantaged communities. Poor glycaemic control exacerbates this burden by increasing retinal, renal, and cardiac damage and raising healthcare costs. This predicament underscores the urgent need for research into cost-effective approaches to preventing diabetes complications. An important but often overlooked strategy to improve metabolic control in diabetic patients is the treatment of periodontitis. Our aim is to assess whether the inclusion of periodontitis treatment in diabetes management strategies can effectively improve metabolic control, and to advocate for its inclusion from an equity perspective. We conducted a comprehensive review of the literature from 2000 to 2023. We analyzed the pathophysiological links between periodontitis, diabetes, and atherosclerotic cardiovascular disease, all of which have inflammation as a central component. We also examined the inequalities in health care spending in this context. Our findings suggest that incorporating routine screening and treatment of periodontitis into national health programs, with coordinated efforts between physicians and dentists, is a cost-effective measure to improve metabolic control, reduce complications and improve the overall quality of life of people with diabetes.